Organizational Memory and the Reutilization of the Technical Knowledge in an Electro-electronic Segment Company in Brazil - Spiller, Arnaldo; Pontes, Cecília Carmen Cunha (Review of Business Management, 2007)
The objective of this article is to present the results of a case study research that investigated the existence of practices that foster and promote explicit technological organizational memory, i.e., documented knowledge, as well as those practices related to the reuse of this knowledge for problem solving. Organizational memory can be defined as the organization's ability to benefit from its past experience in responding more effectively in the present, characterized by the institutionalization of individual’s knowledge. The company investigated is a multinational company from the electro-electronic segment. Several sites were included in the study. The employees were surveyed by means of a Likert-scale questionnaire for the quantitative analysis where the factorial analysis was applied. The overall results indicated that although the employees recognize the importance to grow the explicit technological organizational memory, and valorize the memory processes, such processes do not occur in an effective way in the company. Furthermore, the respondents indicated the availability of enough collective information for them to solve their technical problems. Key-words: Organizational learning. Knowledge management. Electronic industry